Financial contagion in the BRICS stock markets: an empirical analysis of the Lehman Brothers collapse and European sovereign debt crisis - Pereira, Dirceu Rodolfo Coelho (2017)
Dissertação de mestrado em Economia Monetária Bancária e Financeira